Vitamin D Status in Relation to the Clinical Outcome of Hospitalized COVID-19 Patients - Hafez, Wael; Saleh, Husam; Arya, Arun; Alzouhbi, Mouhamad; Fdl Alla, Osman; Lal, Kumar; Kishk, Samy; Ali, Sara; Raghu, Srinivasa; Elgaili, Walaa; Abdul Hadi, Wissam (Frontiers in Medicine, 2022)
Coronavirus Disease (COVID-19) is a newly emerged infectious disease that first appeared in China. Vitamin D is a steroid hormone with an anti-inflammatory protective role during viral infections, including SARS-CoV-2 infection, via regulating the innate and adaptive immune responses. The study aimed to investigate the correlation between serum 25-hydroxyvitamin D (25[OH]D) levels and clinical outcomes of COVID-19. This was a retrospective study of 126 COVID-19 patients treated in NMC Royal Hospital, UAE. The mean age of patients was 43 ± 12 years. Eighty three percentage of patients were males, 51% patients were with sufficient (> 20 ng/mL), 41% with insufficient (12–20 ng/mL), and 8% with deficient (<12 ng/mL) serum 25(OH)D levels. There was a statistically significant correlation between vitamin D deficiency and mortality (p = 0.04). There was a statistically significant correlation between 25(OH)D levels and ICU admission (p = 0.03), but not with the need for mechanical ventilation (p = 0.07). The results showed increased severity and mortality by 9 and 13%, respectively, for each one-year increase in age. This effect was maintained after adjustment for age and gender (Model-1) and age, gender, race, and co-morbidities (Models-2,3). 25(OH)D levels (<12 ng/mL) showed a significant increase in mortality by eight folds before adjustments (p = 0.01), by 12 folds in Model-1 (p = 0.04), and by 62 folds in the Model-2. 25(OH)D levels (< 20 ng/mL) showed no association with mortality before adjustment and in Model-1. However, it showed a significant increase in mortality by 29 folds in Model-3. Neither 25(OH)D levels (<12 ng/mL) nor (< 20 ng/mL) were risk factors for severity. Radiological findings were not significantly different among patients with different 25(OH)D levels. Despite observed shorter time till viral clearance and time from cytokine release storm to recovery among patients with sufficient 25(OH)D levels, the findings were statistically insignificant. In conclusion, we demonstrated a significant correlation between vitamin D deficiency and poor COVID-19 outcomes.